Micro dynamics and macro stability in inventor networks - Michael Fritsch; Muhamed Kudic (The Journal of Technology Transfer, 2021)
From a macro perspective, inventor networks tend to generate remarkably stable structures over time. At the same time, we observe highly dynamic processes at the micro level, in terms of inventor entries and exits as well as formations and terminations of collaborative relationships between them. In order to explain this—at least at the first glance—contradicting pattern, we investigate processes at the intermediate network level. Our analysis draws upon co-patenting data for the entire population of West German inventors in the field of laser technology research from the onset of the technology in the early 1960s over a period of 45~years. Our findings suggest that the key factor for maintaining structural stability of networks is that directly linked partners of inventors with stabilizing properties—so-called 'key players'—take over this function in a subsequent period. We show that processes at the intermediate network level provide new insights on the co-existence of micro fluidity and macro stability in complex adaptive systems.
Keywords: D22; D85; L23; O3; 600; Inventor network; Network stability; Key-player analysis; Innovation; Laser technology